A study on the psychological and social factors related to exercise addiction among middle-aged and elderly people - Pengju Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Middle-aged and elderly people sports participation is favorably connected with their body image. The link of sports participation of Middle-aged and elderly people is based on the nature of the sport and how Middle-aged and elderly people perceive their body size, and they will have a calculating attitude about whether the effect of their participation will be beneficial or negative. As a result, the sports interest has a significant impact on the participation of women in sporting activities. One of the impediments to Middle-aged and elderly people participating in sports is the patriarchal attitude that women should not participate in hard physical activity in front of their male counterpart. This study has analyzed the correlation between sports participation and sports interest. Where, sports participation is used as independent variable and sports interest is used as dependent variable. The data was collected from 60 sports women. This paper has used SEM PLS 3 and AMOS 26 for data analysis. The results indicated that there is a significant association between sports participation and sports interest. The results for Cronbach’s Alpha and Composite Reliability were also significant.